Bone-Related Extramedullary Disease in Newly Diagnosed Myeloma Patients is an Independent Poor Prognostic Predictor - Ying Wang; Aijun Liu; Tingting Xu; Jiahui Yin; Wenming Chen (Clinical Medicine Insights: Oncology, 2022)
Background: Bone-related extramedullary disease (EMD-B) is mass of clonal plasma cells derived from adjacent bone lesions and has obvious heterogeneities in clinical outcomes. This retrospective study aims to evaluate the treatment outcomes and long-term prognosis of newly diagnosed myeloma patients with EMD-B. Methods: This was a retrospective study conducted in Beijing Chaoyang Hospital from January 1, 2010 to December 31, 2019. Seventy-seven newly diagnosed multiple myeloma patients with EMD-B were selected. Propensity score matching (1:2) was used to match patients with and without EMD-B. After matching, 132 patients without extramedullary disease (non-EMD) were included in the study. All patients received bortezomib-based regimens as induction therapy. Results: After matching, baseline data of the 2 groups were comparable. The Cox regression analysis of patients with EMD-B showed that age, paravertebral lesions, and immunoglobulin D (IgD) type may have adverse effects on survival. Bone-related extramedullary disease at new diagnosis was a risk predictor of survival (hazard ration [HR] = 1.80, 95% confidence interval [CI]: 1.09-2.98, P  = .022). The median survival time of the EMD-B group was significantly shorter than that of the non-EMD group (52 months vs 96 months, P  = .043). Induction therapy did not show any significant differences in effectiveness between the 2 groups. Autologous stem cell transplantation (ASCT) significantly increased complete remission rate of patients with EMD-B (EMD-B vs non-EMD: no ASCT 15.7% vs 31.9%, P  = .035; ASCT 42.3% vs 48.8%, P  = .626) and improved their median overall survival rate (EMD-B vs non-EMD: no ASCT 49 months vs 75 months, P  = .003; ASCT not reached vs 96 months, P  = .505). Conclusions: This study demonstrated that newly diagnosed myeloma patients with EMD-B had poor outcomes, which could be improved by ASCT.